Marketing Mix Strategy to Increase Consumer Interest in Choosing Educational Institutions - Suwidiyanti Suwidiyanti; Renny Oktafia; Budi Haryanto (International Consortium of Education and Culture Research Studies, 2020)
In order to create high quality educational institutions that be able to compete with other educational institutions and increase consumer interest in choosing these institutions, the proper marketing strategy is needed, for example marketing mix. The purpose of this study is to describe how marketing mix strategy increase consumer interest in choosing educational institutions. This study used a qualitative research method with a case study research approach. The results of this study are the marketing mix strategy in Sidoarjo SMAMDA consisting of 7P, namely (1) Product, the products offered to consumers are adjusted in the school's vision, namely Islamic, Excellent, and Synergy with boarding school and regular programs; (2) Price (cost), the amount of costs adjusted to the operational costs of the school. The school also provides scholarships for tuition fees and achievements; (3) Place (location), the location of the school is very strategic because it is easy to reach and access both private vehicles and public transportation; (4) Promotion, school promotion activities through social media, online news, magazines, banners, brochures, socialization in junior high schools, and developing a network of partnerships with several schools and universities in Thailand; (5) Human Resources, educational activities are supported by teachers and education staff that corrsponding with their competencies and qualifications; (6) Pshycal evidence, schools have complete, good, and well-maintained facilities and satisfied all of their students' needs; (7) Process, the learning process applies a holistic education model and satisfied the National Education Standards.